Strengthening macro economic policy modeling and analysis in Nigeria - Nwafor, Manson; Rhoe, Valerie; Salau, Sheu (International Food Policy Research Institute, 2009)
The Computable General equilibrium (CGE) model has been successfully used to inform macro and micro policymaking in many developed countries. In developing countries like Nigeria, their influence on policy is limited - in spite of their proven usefulness - due to the low number of people who understand them and/or use them appropriately. Therefore, this workshop was designed to assist with these limitations by acquainting participants with introductory knowledge of CGE modeling with use of the GAMS software (Appendix 1). The specific objectives were: · Expose participants to a policy planning tool, the CGE Model · Acquaint participants with the Nigeria 2006 Social Accounting Matrix (SAM) · Study the effect of policy scenarios on growth and poverty eradication in Nigeria. It was attended by 21 participants drawn from various government departments, research institutions, and universities.